'What happens after saying no?' Egyptian Uprisings and Afterwords in Basma Abdel Aziz's The Queue and Omar Robert Hamilton's The City Always Wins. Issue 2 (August 2018) - Moore, Lindsey
Abstract : This article compares two creative continuations to the 2011–13 Egyptian uprisings: Basma Abdel Aziz's dystopian novel The Queue (Melville House, 2016; al-Tābour, 2013) and Omar Robert Hamilton's semi-autobiographical fiction The City Always Wins (Faber & Faber, 2017). These two novels, written in the bitter aftermath of Egypt's spectacular twenty-first century revolts, share a morbid tonality and concomitantly sceptical outlook toward representation, despite their different generic affiliations. They nevertheless both gamble on the performative potential of creative fiction. In the context of an ostensibly failed revolution, we need to ask what kinds of reader response are evoked by literary diagnoses of the present that flirt with alexithymia (the inability to describe feeling); in other words, how a counterfuturistic afterwardly aspires to be productive. I argue that these two novels, as afterwords on a revolution, animate a tensile present that sediments a century of thwarted popular aspirations, enfolds critical temporalities, and resists closure. The article uses the concepts of achrony and 'robbed time' to define the afterwardly as creative, counter-textual provocation – skirmishes that continually reterritorialise the political and material ground.